La couverture de Bruxelles en tant que lieu de vie par les journaux belges - Joke Bauwens; Pascal Verhoest; Petrus te Braak (Brussels Studies, 2022)
Brussels’ overwhelmingly negative depiction in the press is a frequently mentioned but little researched factor in explaining its lack of appeal as a place to live. This study examines how city life is framed in Belgian newspapers as well as how said frames resonate with broader cultural schemes that influence public perceptions. Using multiple correspondence analysis, we found that the press by and large groups concepts into two diametrically opposed frames: the first corresponding to a phobian perception of Brussels that centres on the negative aspects of city life and the second to a cosmopolitan view of the capital that focusses on its vibrant nature and other inherent advantages. Furthermore, differences between newspapers in their portrayal of life in Brussels relate more so to their orientation (elite versus popular) rather than to their language (Dutch versus French).